Analytical Solution for Advection-Dispersion Equation of the Pollutant Concentration using Laplace Transformation - Paudel, Keshav; Bhandari, Prem Sagar; Kafle, Jeevan (Journal of Nepal Mathematical Society, 2021)
We present simple analytical solution for the unsteady advection-dispersion equation describing the pollutant concentration C(x; t) in one dimension. In this model the water velocity in the x-direction is taken as a linear function of x and dispersion coefficient D as zero. In this paper by taking k = 0, k is the half saturated oxygen demand concentration for pollutant decay, we can apply the Laplace transformation and obtain the solution. The variation of C(x; t) with different times t upto t → ∞ (the steady state case) is taken into account advection-dispersion equation in our study.